2014
DOI: 10.2147/ahmt.s62231
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic conditions in teenage adolescents in Nigeria

Abstract: BackgroundSkin disorders are common in adolescents, and the impact on quality of life can be enormous, particularly when viewed against the backdrop of the visibility of skin diseases and the psychologically vulnerable period of adolescence. However, few studies have documented the magnitude of skin disorders in this subset of individuals. We therefore estimated the point prevalence and pattern of dermatologic conditions in adolescents attending various secondary schools in Calabar, Southern Nigeria.MethodsUsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
(74 reference statements)
3
22
1
2
Order By: Relevance
“…[19][20][21] Community-based studies in Nigeria have reported prevalence rates of skin diseases (or dermatophytoses alone) between 10% and 64%. 1,13,[22][23][24][25][26][27] The most common skin condition was fungal infections, especially tinea capitis among school-age children, especially boys, accounting for 43% of the skin diseases in the community. 1,13,22,23,25 Other common skin conditions were impetigo, 13,24 scabies, miliaria, pyoderma, 13 and tribal marks.…”
mentioning
confidence: 99%
“…[19][20][21] Community-based studies in Nigeria have reported prevalence rates of skin diseases (or dermatophytoses alone) between 10% and 64%. 1,13,[22][23][24][25][26][27] The most common skin condition was fungal infections, especially tinea capitis among school-age children, especially boys, accounting for 43% of the skin diseases in the community. 1,13,22,23,25 Other common skin conditions were impetigo, 13,24 scabies, miliaria, pyoderma, 13 and tribal marks.…”
mentioning
confidence: 99%
“…6 A female preponderance (57.2%) was noted in a study by Henshaw et al, on teenage adolescents in Nigeria, in contrast to our study. 7 The male preponderance in our study maybe due to more chance for male teenagers to get medical help because of their mobility in our society than females.…”
Section: Discussionmentioning
confidence: 70%
“…Berbagai penyakit kulit, baik infeksi maupun non infeksi, sering terjadi pada remaja dengan prevalensi berkisar 58,3% hingga 72,1% di Nigeria. 5 Pada penelitian ini, angka prevalensi penyakit kulit yang ditemukan pada remaja sekolah asrama lebih tinggi, yaitu 85,8%.…”
Section: Pembahasanunclassified